2021
DOI: 10.36663/tatefl.v2i2.172
|View full text |Cite
|
Sign up to set email alerts
|

EFL Pre-Service Teachers’ Perception of Their Readiness in Teaching Online during Covid-19 Pandemic

Abstract: As teacher candidate, students majoring in English Education is required to take a teaching practice in real classroom setting. However, due to Covid-19 pandemic, the scheme of teaching practice is changed to online setting. The current study investigated pre-service teachers’ perception of their readiness in teaching English online. This study was a qualitative study followed by five English teacher candidate. The data were collected using interview guide and were analyzed using thematic analysis. It was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The results of this study are consistent with the findings of previous study who developed HOTS-based thematic question banks in elementary schools showed good results related to the questions they developed (Fadilah et al, 2021). Likewise with the research findings who found that the development of HOTS questions in thematic material had an influence on students' thinking power (Desyandri et al, 2021;Dewi, 2021;Suarti & Ramadhani, 2022). In this case students are able to think critically and creatively in solving a question.…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study are consistent with the findings of previous study who developed HOTS-based thematic question banks in elementary schools showed good results related to the questions they developed (Fadilah et al, 2021). Likewise with the research findings who found that the development of HOTS questions in thematic material had an influence on students' thinking power (Desyandri et al, 2021;Dewi, 2021;Suarti & Ramadhani, 2022). In this case students are able to think critically and creatively in solving a question.…”
Section: Discussionsupporting
confidence: 91%
“…The students realize that learning process activities like this are carried out for their good, their future and to overcome the spread of the disease that is currently endemic. With this self-awareness, students pay close attention and try to achieve maximum learning outcomes (Cohen et al, 2020;Dewi, 2021). However, this research notes that the learning outcomes obtained by students are still low in several materials, such as mathematics, physics and chemistry.…”
Section: Discussionmentioning
confidence: 96%
“…Primary school English teachers play a crucial role in laying the foundation for a child's linguistic and cognitive development. These educators are instrumental in shaping the language skills of young learners, helping them build a strong command of English from the early stages of their education (Das, 2019;Dewi, 2021). The importance of a primary school English teacher extends beyond mere language acquisition; these professionals foster a love for reading, writing, and effective communication.…”
Section: Introductionmentioning
confidence: 99%